Respuesta :

sid071

Hey there!!

Let's take the two numbers as 'x' and 'y'

The sum of these two numbers is 36.

... x + y = 36

Twice the first number minus the second is 6.

... 2x - y = 6

Now, we have two equations.

_______________________________________________________

... x + y = 36  

... 2x - y = 6

Now, let's add both the equations.

... 3x = 42

Divide each side by 3.

... x = 42 / 3

... x = 14

Hence, the first number is'14'.

We know the sum of both the numbers is 36.

... x + y = 36

... 14 + y = 36

Subtract 14 on both sides.

... y = 36-14

... y = 22

Hence, the second number is 22.

The numbers are 14 and 22.

Hope my answer helps!!